“Customer awareness in purchasing personal loan at Koperasi Pendidikan Islam Malaysia (Ukhwah) and the elements of marketing mix” / A.Samad A.Hamid - A.Hamid, A.Samad (Faculty of Business and Management, 2009)
Creating customer awareness is a core business challenge which has attracted considerable business attention. There many attributes that can develop customer awareness which are Product, Price, Place and Promotion. Creating customer awareness is vital because when a customer know the existence of a product, customer will tend to purchase if its can satisfy the need of customer. Customer awareness is the major driving force for business sustainability and in today’s competitive global marketplace, it is recognized that high customer awareness is essential for the success of the firm.